2015
DOI: 10.1051/matecconf/20153306006
|View full text |Cite
|
Sign up to set email alerts
|

Electronic and crystal structure of the high entropy TiZrHfCoNiCu intermetallics undergoing martensitic transformation

Abstract: Abstract. It was shown very recently that despite high thermal stability some high entropy alloys, namely, intermetallic compounds of TiZrHfCoNiCu family, undergo martensitic transformation and exhibit shape memory effect [1]. It was also found that X-ray diffraction patterns taken from those compounds resemble qualitatively ones of B2 ordering type for austenitic state and B19` -for martensite. It is going to be shown [2] that the ordered structure of austenite phase is not B2 but is a result of group-subgrou… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
37
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 38 publications
(39 citation statements)
references
References 7 publications
2
37
0
Order By: Relevance
“…Only recovered strain accumulated at 500 MPa varies ( Table 2). The reason for this is related to crystal structure parameter changes in austenitic B2 and martensitic B19' phases, which are described in [39]. Here we shall use only relative volume change during forward MT calculated from volume per atom values for martensite and austenite, which are calculated in their own turn from lattice parameters, taking into account the number of atoms in the unit cell.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Only recovered strain accumulated at 500 MPa varies ( Table 2). The reason for this is related to crystal structure parameter changes in austenitic B2 and martensitic B19' phases, which are described in [39]. Here we shall use only relative volume change during forward MT calculated from volume per atom values for martensite and austenite, which are calculated in their own turn from lattice parameters, taking into account the number of atoms in the unit cell.…”
Section: Resultsmentioning
confidence: 99%
“…5. TiZrHfCoNiCu intermetallics with a stable B2 structure (data taken from [15,39]) have DS mix = 13.211 Jmol…”
Section: Resultsmentioning
confidence: 99%
“…The accuracy of the measurements for the temperatures of the phase transformations was ± 7K. 16.67 compound starts at a lower temperature of 1530 K and the major DTA peak associated with it has a width of about 120 K. Further cooling reveals a small peak around 1200 K.…”
Section: Methodsmentioning
confidence: 89%
“…The peculiar high temperature crystal structure-a triclinically distorted one of the B2 type that carries these distortions into the B19' martensite phase (modeled with the help of ab-initio calculations and confirmed by X-ray diffraction measurements) [16]-was proposed to be the origin of the HESMA yield strength and shape memory behavior enhancement. In this context, it was shown that for the TiZrHfCoNiCu system a B2↔B19' type of martensite transformation takes place [14][15][16]. Recently, an extra six component system CoNiCuAlGaIn, which emulates the B2 NiAl intermetallic compound was introduced [17].…”
Section: Introductionmentioning
confidence: 98%
See 1 more Smart Citation